2020
DOI: 10.3390/antiox9111093
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative Characteristics of Chicken Breast Meat and Blood after Diet Supplementation with Carnosine, L-histidine, and β-alanine

Abstract: The objective of the study was to test the effect of diets supplemented with β-alanine, L-histidine, and carnosine on the histidine dipeptide content and the antioxidative status of chicken breast muscles and blood. One-day-old Hubbard Flex male chickens were assigned to five treatments: control diet (C) and control diet supplemented with 0.18% L-histidine (ExpH), 0.3% β-alanine (ExpA), a mix of L-histidine\β-alanine (ExpH+A), and 0.27% carnosine (ExpCar). After 28 days, chicken breast muscles and blood sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 60 publications
0
27
1
2
Order By: Relevance
“…Sophora koreensis has been known as a traditional herb to treat rheumatoid issues in Korea because of its antioxidant capacity [ 13 , 24 ]. The antioxidant enzymes including SOD, GPx, and catalase are the first factors against antioxidant reactions [ 11 , 12 ]. Antioxidant effects of scopoletin were shown earlier [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sophora koreensis has been known as a traditional herb to treat rheumatoid issues in Korea because of its antioxidant capacity [ 13 , 24 ]. The antioxidant enzymes including SOD, GPx, and catalase are the first factors against antioxidant reactions [ 11 , 12 ]. Antioxidant effects of scopoletin were shown earlier [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Normally, the natural antioxidant defense system is able to prevent cells from oxidative injuries by enzymatic control of free radicals [ 10 ]. Superoxide dismutase (SOD), glutathione peroxidase (GPx), and catalase are the major enzymes to counteract free radicals and diminish the lipid peroxidation rates [ 11 , 12 ]. In addition, the lower antioxidant defense in the body results in the excessive generation of ROS leading to oxidative injuries [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Because the blood TAS level at slaughter age in the T3 group was higher than that of the poultry in T1 group, this may have been caused by the increase in the concentration of carnosine, which has strong antioxidant ability (O'Neill et al, 1998;Cong et al, 2017;Kralik et al, 2018;Qi et al, 2018;Kopec et al, 2020;Shimamoto et al, 2020). These studies reported that the antioxidant capacity of the PM increased with the βA supplement (Qi et al, 2018).…”
Section: Resultsmentioning
confidence: 94%
“…Histidina yang juga berfungsi sebagai antioksidan hanya dijumpai pada S. aquifolium (50,21 mg/L). Suplementasi histidina dapat menghambat kerusakan oksidatif oleh paparan Cu di usus (Jiang et al2016;Kopec et al 2020).…”
Section: Profil Asam Aminounclassified